Francophone Afropean literatures - Hitchcott, Nicki; Thomas, Dominic (Liverpool University Press, 2014)
What does Afro-Europe signify? This volume explores the concept and possibility of a black European community by analysing the ways in which contemporary Francophone African writers articulate and interrogate their complex relationships with European society, culture and history. Readers will discover the symbiotic ways in which Africa has transformed/been transformed (in/by) Europe and in turn how Africanness has (re)defined Europeanness. To this end, the volume places scholarly essays addressing the relationship between the francophone and Afro-European context alongside short stories and essays by some of the most critically-acclaimed and influential producers of Afropean writing today: Fatou Diome, Alain Mabanckou, Léonora Miano, Wilfried N'Sondé, Sami Tchak and Abdourahman Waberi. Works by these authors are discussed in and across the scholarly interventions, generating dialogue around what it means to be ‘Francophone’ and ‘Afropean’ in the twenty-first century. At a time when it is no longer easy to define what Europe really is, this book considers to what extent the category ‘Afropean’ may prove helpful in improving our understanding of the complex ways in which minority communities conceive of identity in Europe today and address the range of issues impacting them. The notion of ‘Afropeanism’ is of course relatively new, and this book does not claim to offer an exhaustive analysis of the term's usage and/or potential pertinence. Rather, the cultural, political, and social circumstances of Europe today are reflected in discussions surrounding the term and perhaps not surprisingly, in the diverse and diverging perspectives adopted by the scholars and creative writers.